2011
DOI: 10.4271/2011-01-0328
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Performance and Emissions of an Automotive Euro 5 Diesel Engine Fuelled with B30 from RME and JME

Abstract: The effects of using a B30 blend of ultra low sulphur diesel and two different Fatty Acid Methyl Esters (FAME) obtained from both Rapeseed Methyl Ester (RME) and Jatropha Methyl Ester (JME) in a Euro 5 small displacement passenger car diesel engine on both full load performance and part load emissions have been evaluated in this paper.In particular the effects on engine torque were firstly analyzed, for both a standard ECU calibration (i.e. without any special tuning for the different fuel characteristics) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…As mentioned before, this increment is obtained by means of the CLC operation that oversees the fuel quantity augment without changing the engine calibration. It is worth noting that, with a specific calibration, changing the injection setting and boost conditions, a higher torque increment with respect to the present results could be reached, as already demonstrated by Millo et al in recent experiences. The effect is the λ reduction, as observed in the right plot of Figure .…”
Section: Resultssupporting
confidence: 85%
“…As mentioned before, this increment is obtained by means of the CLC operation that oversees the fuel quantity augment without changing the engine calibration. It is worth noting that, with a specific calibration, changing the injection setting and boost conditions, a higher torque increment with respect to the present results could be reached, as already demonstrated by Millo et al in recent experiences. The effect is the λ reduction, as observed in the right plot of Figure .…”
Section: Resultssupporting
confidence: 85%
“…Again in this case, RME does not show any considerable variations in number distribution, compared to diesel fuel, while an appreciable reduction can be observed in the mass size distribution, with a peak diameter at about 50 nm and 100 nm, respectively, for both fuels; conversely, at this engine operating condition, JME leads to a remarkable increase in PN, as well as in particle mass, with almost doubled peak distribution values compared to diesel fuel; while an appreciable reduction in number and mass can be also observed for particles below 10 nm. The large increase in particle number measured with JME could, at least in part, be attributed to a slight change in the EGR rate, which is likely to produce a dramatic change in soot emissions, due to the particular setting of the engine calibration point on the soot-NOx trade off which was highlighted in a previous research activity [7]. Therefore, the extremely important effects on PM emissions that can be attributed to shifts in the engine operating points on the calibration maps, highlight the need for a specific adjustment of the engine calibration on the basis of the fuel characteristics (e.g.…”
Section: Experimental Setup and Test Proceduresmentioning
confidence: 82%
“…The large increase in particle number measured with JME could, at least in part, be attributed to a slight change in the EGR rate, which is likely to produce a dramatic change in soot emissions due to the particular setting of the engine calibration point on the soot−NO x trade-off, as shown in Figure 4, and which was highlighted in a previous research activity. 15 Therefore, the extremely important effects on PM emissions that can be attributed to shifts in the engine operating points on the calibration maps highlight the need for a specific adjustment of the engine calibration on the basis of the fuel characteristics (e.g., for the lower LHV of biofuel blends) in order to avoid jeopardizing the potential emission benefits of biofuels.…”
Section: Resultsmentioning
confidence: 99%
“…Exhaust gases were sampled at the engine outlet, downstream of the turbine, and measured through a Fisher-Rosemount NGA-2000 gas analyzer which provided CO, CO 2 , HC, NO x , and O 2 measurements. Smoke detection, in terms of filter smoke number (FSN) was carried out by means of an AVL 415S smoke meter, for the purpose of repeatability checks (a detailed description of the test rig used during this research activity can be found in ref 15).…”
Section: Experimental Setup and Test Proceduresmentioning
confidence: 99%